Urgensi Iffah bagi Masyarakat Sekolah - Nurulhaq, Dadan; Fikri, Miftahul; Azizah, Habibah Nur; Rohmah, Fitria Nada; Sukmara, Ghina Fadlilah (Atthulab: Islamic Religion Teaching and Learning Journal, 2021)
Abstract: This paper aims to find out how urgent iffah is for the school community, which is focused on students at one of the Aliyah Madrasahs, to be precise in Sulawesi. This research is an action research on students by giving a questionnaire consisting of fifteen questions. The research subjects consisted of 50 students. The research data was obtained through documentation of the results of quantitative data collection. Data analysis used quantitative descriptive analysis technique. data validation using the method triangulation technique. The results showed that currently 70% of students have implemented the nature of iffah in their daily lives. Familiarize yourself with good things between each other and keep yourself away from all the prohibitions of Allah SWT. shows that students are trying to carry out iffah. The nature of iffah according to Ibn Masawaih in his book tahdzibul akhlaq, is an ability that humans have to withstand the impulses of their passions. The nature of iffah has its derivative properties, namely al-haya, qana'ah, sakho, and waro. And in practice, the nature of iffah is divided into 2, namely refrain from pubic lust and refrain from abdominal lust. Abstrak: Tulisan ini di bertujuan untuk mengetahui seberapa urgen iffah bagi masyarakat sekolah, yang di fokuskan kepada para siswi di salah satu Madrasah Aliyah tepatnya di Sulawesi. Penelitian ini merupakan penelitian tindakan terhadap siswa dengan memberi kuisioner yang terdiri dari lima belas pertanyaan. Subjek penelitian terdiri dari 50 siswa. Data penelitian diperoleh melalui dokumentasi hasil pengumpulan data kuantitatif. Analisis data menggunakan Teknik analisis deskriptif kuantitatif. Validasi data dengan menggunakan Teknik triangulasi metode. Hasil penelitian menunjukkan bahwa pada saat ini 70% siswa sudah menerapkan sifat iffah dalam kesehariannya. Membiasakan diri dengan hal-hal baik antar sesama dan menjaga diri dengan menjauhi segala larangan Allah swt. menunjukkan bahwa siswi memang berusaha melaksanakan iffah. Adapun Sifat iffah menurut Ibnu maskawaih di dalam kitabnya tahdzibul akhlaq, ialah suatu kemampuan yang dimiliki manusia untuk menahan dorongan hawa nafsunya. Sifat iffah mempunyai turunan turunan sifat, yakni al-haya, qana’ah, sakho, dan waro. Dan dalam pengamalannya, sifat iffah terbagi 2, yakni menahan diri dari syahwat kemaluan dan menahan diri dar syahwat perut.